Assessment and treatment of irruptive cancer pain - Santos, Juliana (2015)
The breakthrough cancer pain (BTCP) consists of a transitory exacerbation of pain that occurs either spontaneously or triggered by a specific factor (predictable or unpredictable), despite the relatively stable and adequate control of the background pain. It is essential to clearly identify that it is an episode of BTP and not a poorly controlled chronic pain.Pharmacological treatment can consist of rescue medication - Short Acting Opioid - SAO (eg. Sevredol®, Oramorph®) and Rapid Opioid Onset - ROO such as sublingual fentanyl sublingual, buccal film and transmucosal (eg. Abstral®, Breakyl® and Actiq®).It is essential nurses know how to make a proper assessment of BTP, how to teach the patient to manage the therapeutic regimen and how to reassess. The objectives of the reassessment determine the efficacy and tolerability of treatment of BTP and any change in its nature. Improper reassessment could lead to the continuation of an ineffective and/or inappropriate treatment.